2014
DOI: 10.1111/bjh.13118
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Haematological recovery after autologous stem cell transplantation is associated with favourable outcome in acute myeloid leukaemia

Abstract: SummaryAutologous stem cell transplantation (ASCT) is applied to consolidate first remission in patients with acute myeloid leukaemia (AML). However, outcome after ASCT widely varies among AML patients. We analyzed the prognostic significance of haematological recovery for neutrophils [absolute neutrophil count (ANC) >1Á0 9 10 9 /l] and platelets (platelet count >20Á0 9 10 9 /l), stratifying at day 20 after ASCT in 88 consecutive and homogeneously treated AML patients in first remission. We observed that patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Recently it was shown that engagement of the inhibitory receptors on macrophages and dendritic cells delivers a suppressive signal from the T cell to the myeloid cell [5557]. Thus, the interaction between PD-1 and PD-L1/2 is likely to have a bi-directional effect.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that engagement of the inhibitory receptors on macrophages and dendritic cells delivers a suppressive signal from the T cell to the myeloid cell [5557]. Thus, the interaction between PD-1 and PD-L1/2 is likely to have a bi-directional effect.…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, it offers distinct anti-leukemic effectiveness and prolongs survival similar to allogeneic transplantation while avoiding morbidity and mortality of graft versus host disease associated with allogeneic transplantation [2,17]. However, prospective studies in elderly AML patients comparing chemotherapy consolidation with autologous stem cell transplantation (ASCT) or allogeneic transplantation are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies including various AML subtypes, we have observed a wide variation in mobilized circulating CD34+ cells at the day of peripheral stem cell collection after two induction cycles [11][12]. We identified a poor stem cell mobilization potential (CD34+ low ) to predict favorable long-term outcome after autologous SCT, whereas high levels of mobilized CD34+ cells (CD34+ high ) were associated with adverse outcome.…”
Section: Lettermentioning
confidence: 76%